46. Motor Evoked Potentials and clinical heterogeneity at onset in ALS. Issue 1 (January 2015) - Ferigo, L.; Rossi, F.; Piccoli, D.; Costa, B.; Del Colle, R.; Polo, A.
<x xml:space="preserve">Abstract</x> The pathophysiology of Motor Evoked Potentials (MEPs) changes in Amyotrophic lateral sclerosis (ALS) patients have been related to phenotype, the site of onset and clinical course; the diagnostic impact is not as relevant as to be considered in diagnostic criteria. We attempted to correlate the variability of MEPs in patient with ALS, with different clinical involvement at onset. Patients were classified according to site of onset (bulbar, upper or lower limb);the time of onset was estimated from the appearance of the first relevant clinical symptom. We examined 20 patients (10 males, 10 females, mean age onset 68 years old ranging from 50 to 88 years old) with ALS. MEP features included measurements of resting motor threshold (RMT), cortical silent period (CSP) and central conduction time (CCT) both from upper (UL) and lower limbs (LL). Main findings: (1) abnormalities of LL-RMT (elevated) are frequent in patients with lower limb onset (60%) and bulbar onset (60%); (2) absent of LL-SP was found in patients with lower limb onset (90%); (3) prolonged UL-SP was found in patients with lower limb onset (25%); (4) prolonged LL-CCT was found in patients with lower limb onset (100%) and both from upper and lower limbs in bulbar onset (90%). Taking into account the picture of clinical onset in our ALS patients, MEPs have shown simultaneous abnormalities in non contiguous sites.